Prevalence and related factors of cognitive frailty in diabetic patients in China: a systematic review and meta-analysis - Peng, Junjie; Ming, Limei; Wu, Jiaming; Li, Yunchuan; Yang, Shuhua; Liu, Qin (Frontiers in Public Health, 2023)
Abstract Objective: Cognitive frailty (CF) is characterized by physical frailty and potentially reversible cognitive impairment without Alzheimer's disease and other dementias. Clarifying the prevalence and related factors of cognitive frailty can help researchers understand its epidemiological status and formulate intervention measures. This study aims to conduct a systematic review and meta-analysis of the prevalence and related factors of CF in diabetic patients in Chinas to better understand the current status of CF in diabetic patients in China and develop effective intervention measures for related factors. Methods: PubMed, Web of Science, Embase, Cochrane Library, CNKI, Weipu(VIP), WANFANG, China Biology Medicine (CBM) and DUXIU were searched to collect epidemiological data on Chinese diabetic patients. Articles published through May 29, 2023, were searched. The number of diabetes with CF and the total number of diabetes in the included studies were extracted to estimate the prevalence of diabetes with CF. For factors related to diabetes with CF, odds ratios (OR) and 95% confidence intervals (CI) were used for estimation. Results: A total of 248 records were screened, of which 18 met the inclusion criteria. The results of meta-analysis showed that the prevalence of Chinese diabetic patients with CF was 25.8% (95% CI = 19.7% to 31.9%). Subgroup analysis showed that hospital prevalence was higher than in the community and in women than in men. Combined estimates showed that depression, malnutrition, advanced age (≥70, ≥80), combined chronic diseases ≥4 and glycated hemoglobin ≥8.5 were risk factors for CF in diabetics patients in China, with regular exercise and high education level (≥ college) as protective factors. Conclusion: Cognitive frailty was common in diabetic patients in China. Such populations should be screened early and intervened with relevant factors. REGISTRATION: PROSPERO ID: CRD42023431396.